The stray moth - Chua, Barnabas Zhong Li (Nanyang Technological University, 2020)
The Stray Mothis a 13 minutes 43 seconds short film Final Year Project produced by Cultural Orphan Films. The production team consists of four members, Barnabas Chua Zhong Li, Tan Pat Hoon Megan, Chua Shu Ern and Huang Jun Yao Kenneth, undergraduates from Nanyang Technological University, Wee Kim Wee School of Communication and Information (WKWSCI).The Stray Mothrevolves around the themes of Identity and Culture. It tells the story of a man with a dark secret, who struggles to find closure after the death of his wife.But when he encounters the strange world of Getai (歌台), he is forced to face his true identity.This report will illustrate the whole process the team went through from pre-production, to production and post production.